Interactions between microtopography, root exudate analogues and temperature determine CO2 and CH4 production rates in fire-degraded tropical peat. (June 2022) - Akhtar, Hasan; Lupascu, Massimo; Sukri, Rahayu S.
Abstract: Repeated fires can alter the microtopography, vegetation composition, peat surface temperature and can increase the risk of flooding in tropical peatlands. However, difficult site conditions limit our understanding of these critical factors regulating greenhouse gas (GHG, viz . CO2 and CH4 ) production and emissions from fire-degraded tropical peatlands. We aimed to relate the complex interactions between peat oxic and anoxic conditions due to changes in microtopography, labile C inputs in the form of plant root exudates (from ferns and sedges), and diurnal temperature change in affecting CO2 and CH4 production from fire-degraded tropical peat. We found that the mesic condition, which reflects the field moisture or water-saturated oxic conditions in hummocks, acted as a strong source of CO2 (230 ± 29 μgCO2 g −1 hr −1 ) and weak sink for CH4 (−5.6 ± 0.2 ngCH4 g −1 hr −1 ), while anoxic acted as a weak source of CO2 and strong source of CH4 (61.3 ± 6.2 μgCO2 g −1 hr −1 ; 592 ± 111 ngCH4 g −1 hr −1 ). Addition of labile C enhanced both the CO2 and CH4 production across treatments by five and two times for the two gases, respectively. Temperature sensitivity (Q10 ) for CO2 was higher for peat incubated under mesic conditions (1.21 ± 0.28) whereas for CH4 it was higher in peat under anoxic conditions (1.56 ± 0.35). Collectively, our result highlights how microscale changes in microtopography coupled with the quality and quantity of labile C and temperature variation can regulate GHGs production from fire-degraded tropical peatland areas, which are projected to increase with frequent fire episodes and future climate warming in the region. More importantly, changes in these critical factors may result in a net positive carbon emission with long-term elevated CH4 production and emissions rates from such fire-degraded tropical peatland areas. Highlights: Microtopography conditions enhances GHG production from fire-degraded tropical peat. Anoxic condition enhances CH4 production whereas oxic enhances CO2 production. Labile C addition enhances both the CO2 and CH4 production across conditions. Anoxic condition shows higher temperature sensitivity for CH4 whereas mesic for CO2 .